The European venture capital landscape: an EIF perspective. Volume V: The economic impact of VC investments supported by the EIF - Elitsa Pavlova; Simone Signore (European Investment Fund (EIF), 2019)
This paper examines the impact of venture capital (VC) investments supported by the EIF on the financial growth and performance of young and innovative firms. Using a novel dataset covering European start-ups supported by VC in the years 2007 to 2014, we generate a counterfactual group of non-VCbacked firms through a combination of exact and propensity score matching. To offset the relatively limited set of observables allowed by our data, we estimate treatment propensity using a series of innovative measures based on machine learning, network theory, and satellite imagery analysis. Our results document the positive effects of EIF-supported VC investments on start-up performance, as measured through various financial indicators (e.g. assets, revenue, employment). We find that VC financing enables start-ups to prioritise long-term growth, trading off short- to medium-term profitability if necessary. Overall, our work provides meaningful evidence towards the positive effects of EIF-supported VC investment on the financial growth of young and innovative businesses in Europe.
Keywords: G24; L25; M13; O38; 330; EIF; venture capital; public intervention; real effects; start-ups; machine learning; geospatial analysis; network theory